Research on enterprise financing credit based on soft and hard information under the background of blockchain: Take high-tech enterprises in Anhui Province as an example - Lin, Kairan (International Journal of Global Economics and Management, 2024)
Under "accelerating the formation of a new development pattern of domestic circulation and domestic and internationaldouble circulation mutually promoting", high-tech enterprises, as an important role in promoting scientific and technological innovation and economic development, are facing the dilemma ofdifficult and expensive financing. This paper establishes acharacteristic evaluation and credit guarantee systembased on big data credit model to explore the difference ofsoft and hard informationon financing of high-tech enterprises in Anhui Province under the background of double circulation. Taking 131 high-tech enterprises in Anhui Province as samples, this paper analyzes the influence of unstructured soft information and structured hard information on credit evaluation and its intensity byhierarchical linear regression model. The results show that soft and hard information indexes have significant positive effects on credit risk of high-tech enterprises, and soft information has more obvious effects on small and medium-sized high-tech enterprises.